Circle of Willis Variants and Their Association with Outcome after Successful Revascularization of Anterior Large Vessel Occlusion - Sriwastwa, Aakanksha; Oswald, Michael K.; Vagal, Achala S.; Demel, Stacie L.; Zhang, Bin; Voleti, Sriharsha; Ali, Arafat; Morgan, Daniel; Thompson, Trevor; Vidovich, Johnathan; Aziz, Yasmin N.; Wang, Lily Li-Li. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Leptomeningeal collaterals have been associated with better outcomes in large-vessel stroke, but little is known about how the Circle of Willis (CoW) collaterals affect stroke outcomes. We aimed to determine the relationship between three anatomically distinct CoW subtypes and 90-day outcomes in acute ischemic stroke patients after successful revascularization via endovascular thrombectomy (EVT).MATERIALS AND METHODS: We performed a retrospective analysis of patients treated with successful EVT for large-vessel occlusion at a comprehensive stroke center between May 2016 and November 2023. The CoW anatomy was trichotomized using baseline computed tomography angiography as follows: (I) complete CoW (C-CoW), (II) non-isolating incomplete CoW (NI-CoW), and (III) isolating incomplete CoW (I-CoW). Chi-squared and logistic regression analyses were utilized to determine the association of the CoW subtype with two co-primary outcomes: the 90-day modified Rankin Scale and 90-day mortality.RESULTS: A total of 465 patients were included in the analysis. Multivariable logistic regression analysis demonstrated a significant association between I-CoW and 90-day mRS compared to NI-CoW [OR (95% CI), 1.83 (1.08-3.09); p=0.02]. Additionally, I-CoW anatomy was associated with a higher 90-day mortality than C-CoW [OR (95%CI), 2.58 (1.01-6.60); p=0.04] and NI-CoW [OR (95% CI), 1.89 (1.13-3.18); p=0.01].CONCLUSIONS: CoW variants are associated with functional and mortality outcomes in patients treated with endovascular thrombectomy for anterior circulation large vessel occlusion. Further research is needed to determine how CoW vessel anatomy may impact clinical assessment, triage, and treatment in acute ischemic stroke.ABBREVIATIONS: CoW = Circle of Willis; EVT = endovascular thrombectomy; C-CoW = complete Circle of Willis; NI-CoW = non-isolating incomplete Circle of Willis; I-CoW = isolating Circle of Willis; AIS = acute ischemic stroke; LVO = large vessel occlusion; ACom = anterior communicating artery; PCom = posterior communicating artery; Tan CS = Tan collateral scores; ACA = anterior cerebral artery; PCA = posterior cerebral artery.